Fast Hydrothermal Liquefaction of Native and Torrefied Wood. (May 2017) - Tran, Khanh-Quang; Klemsdal, Aksel Junge; Zhang, Wennan; Sandquist, Judit; Wang, Liang; Skreiberg, Øyvind
Abstract: The work presented in this paper aimed to examine the effect of heating rate on the bio-crude yield of wood hydrothermal liquefaction. Three different heating methods were developed, resulting in heating rates ranging from 66 °C/min to 179 °C/min. The experiments were conducted using Norway spruce wood as feedstock at an operation temperature of 350 °C and with a total reaction time of 15 minutes. The bio-crude product was collected and separated using dichloromethane (DCM) as solvent and a centrifugal separator. The results confirm that heating rate has a clear positive effect on the bio-crude oil yield, increasing from 18.9 wt% for the lower heating rate of 66 °C/min to 35.8 wt% for the higher heating rate of 179 °C/min. It is also shown that the effect of feedstock pre-treatment via torrefaction on the bio-crude yield is negative.